ANALISIS PENGELOLAAN PADANG RUMPUT SIKASUR SEBAGAI PARIWISATA MINAT KHUSUS DI SITUBONDO - Rohman, Nur; Manggiasih, Ninda Dwi (Kepariwisataan: Jurnal Ilmiah, 2020)
This study aims to analyze the management system of the Sikasur Savannah tourist destination with special interest. This research is a qualitative study using non-probability sampling techniques, then the data is analyzed using SWOT. The results of this research can be obtained strategies that can be used to manage this tourist spot. The strategies obtained are: (1) Forming an organization that involves the participation of the surrounding community to be trained especially in the field of language so that they are ready to face tourists from outside the region; (2) Adding facilities that do not exist and completing facilities that are lacking so that promotional activities can run smoothly; (3) Add facilities that are felt to be lacking so that they are not left behind by similar types of tourism; (4) Conducting training for the community to later form a special organization so that they can participate in management so that their development becomes smoother; (5) Packaging Sikasur Savannah tourism objects better so that all tourists are interested in visiting. Keywords: Sikasur Savannah, Special Interest Tourism, SWOT Analysis